Potency, Participation, and Development: Insights from Sustainable Tourism of Setigi in Sekapuk Village, Indonesia - Nurotun Waridah (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2021)
Community-Based Tourism (CBT) has become a new trend for local-based development. However, many villages have not developed this potentiality as a new commodity as a tourism-based community. For this reason, this article explains three important elements in the development of community-based tourism in the Sekapuk Village community, Gresik Regency, East Java, namely following the potential, participation, and development of Setigi tourism. This research highlights three critical issues concerning i) how the role of local communities in maximizing village potential, ii) how Community-Based Tourism practices work effectively in increasing community social awareness, and iii) how communities build new tourist destinations. The research method using observation in Setigi tourism, interviews with village leaders, managers of Tourism Awareness Group/Kelompok Sadar Wisata (Pokdarwis), local traders, and visitors. The indication of community has built Setigi tourist destinations by utilizing the potential of nature. Meanwhile, CBT is implemented in environmental conservation, tourism training, accessibility of transformation, and the development of communication systems. Setigi tourism is built based on social participation, which results in nature-based tourism destinations, the development of the Mbok Inggih kitchen, and the home industry. As a successful tourist village development, the village has achieved the icon of the Millionaire Village. Nevertheless, in the end, Setigi tourism still has limitations in optimizing the socio-cultural and socio-religious potential.